International Pediatric Otolaryngology Group (IPOG): Juvenile-onset recurrent respiratory papillomatosis consensus recommendations. (January 2020) - Lawlor, Claire; Balakrishnan, Karthik; Bottero, Sergio; Boudewyns, An; Campisi, Paolo; Carter, John; Cheng, Alan; Cocciaglia, Alejandro; DeAlarcon, Alessandro; Derkay, Craig; Fayoux, Pierre; Hart, Catherine; et al.
Abstract: Objectives: To develop consensus recommendations for the evaluation and management of juvenile-onset recurrent respiratory papillomatosis (JORRP) in pediatric patients. Methods: Expert opinion by the members of the International Pediatric Otolaryngology Group (IPOG). The mission of the IPOG is to develop expertise-based consensus recommendations for the management of pediatric otolaryngologic disorders with the goal of improving patient care. The consensus recommendations herein represent the first publication by the group. Results: Consensus recommendations including diagnostic considerations, surgical management, systemic adjuvant therapies, postoperative management, surveillance, and voice evaluation. These recommendations are based on the collective opinion of the IPOG members and are targeted for otolaryngologists, primary care providers, pulmonologists, infectious disease specialists, and any other health care providers that manage patients with JORRP. Conclusions: Pediatric JORRP consensus recommendations are aimed at improving care and outcomes in this patient population.